Network load traffic on MySQL atomic transaction database - Mohamed, Asghaiyer (Bulletin of Social Informatics Theory and Application, 2020)
Internet technology is developing very rapidly especially on the database system. Today's database has led to data that cannot be processed into the traditional way that we call big data. Some data stored on the server requires a way for the data to be valid and intact for that transaction mechanism appears on RDBMS which ensures that the data stored will become a unified whole as in customer account data, withdrawal of money at ATMs, e-transactions -commerce and so on. Of course the use of transactions in a database by not using Atomic transactions has a difference in terms of traffic on the network. This research appears by analyzing network traffic or density from a database that uses transactions and not to users who access them. This research method uses a questionnaire method by distributing questionnaires quantitatively to 300 respondents. The results of the study of approximately 300 respondents, researchers get the results that the use of transactions in databases and databases without transactions after being accessed by 300 people, the densest network is a network owned by a system that uses transaction features, this is because there is a slight increase of about 13% of traffic when compared to a network without transactions. This statement shows that two-way communication from a database that has the transaction provides feedback to the user so that the data is reliable as an indicator that the data has been stored safely. Further research can be done by finding other information or a study of big data using the atomic transaction model.